(untitled) (Географический вестник=Geographical bulletin, 2017)
Отражен творческий вклад выдающегося лесовода А.Е. Теплоухова в становление лесоводственных знаний и практического лесного хозяйства на Урале. REMARKABLE URAL FORESTRY SCIENTIST (TO 200 YEARS FROM THE DATE OF A BIRTH OF A.E. TEPLOUHOV) The creative input of remarkable forestry scientist A.E. Teplouhov in standing of knavledge and practical forestry in Urals is described.